2015
DOI: 10.1080/15332691.2014.966879
|View full text |Cite
|
Sign up to set email alerts
|

Couple Therapy for Partner Aggression: Effects on Individual and Relational Well-Being

Abstract: The authors examined degrees to which couple therapy for psychological and mild to moderate physical partner aggression improved partners' general distrust in each other and their emotional comfort regarding engaging in a conflict-resolution discussion. A secondary analysis was conducted on data from 55 heterosexual couples who sought treatment at a university-based community clinic. Over the course of therapy, participants exhibited decreased general distrust in their partners, as well as decreased anxiety an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
1
1
0
3
Order By: Relevance
“…These findings are consistent with those of Aslani and colleagues (2019), which demonstrated that domestic violence couple therapy reduced violence against women (Aslani et al, 2020). Moreover, the findings of Valladares Kahn et al (2015) showed that couple therapy significantly impacts reducing aggression and enhancing the psychological well-being and relationships between couples (Valladares Kahn et al, 2015). These results are also in line with other prior findings (Beasley & Ager, 2019;Ganz et al, 2022;Hassannejad et al, 2017;Rathgeber et al, 2019;Saemi et al, 2020;Sheydanfar et al, 2020).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…These findings are consistent with those of Aslani and colleagues (2019), which demonstrated that domestic violence couple therapy reduced violence against women (Aslani et al, 2020). Moreover, the findings of Valladares Kahn et al (2015) showed that couple therapy significantly impacts reducing aggression and enhancing the psychological well-being and relationships between couples (Valladares Kahn et al, 2015). These results are also in line with other prior findings (Beasley & Ager, 2019;Ganz et al, 2022;Hassannejad et al, 2017;Rathgeber et al, 2019;Saemi et al, 2020;Sheydanfar et al, 2020).…”
Section: Discussionsupporting
confidence: 86%
“…Well-being refers to an individual's satisfaction with life, intellectual cultural conditions, goals, expectations, and concerns based on which they live (Hooshmand Kang Sofla et al, 2020;Khanjani et al, 2014). Psychological well-being reflects the quality of life experienced and indicates optimal psychological functioning and experience from one's own life (Asghariebrahimabad & Mamizade, 2018;Hooshmand Kang Sofla et al, 2020;Valladares Kahn et al, 2015). Individuals with high levels of psychological well-being generally experience more positive emotions and have a positive evaluation of events that occur throughout their lives (Asghariebrahimabad & Mamizade, 2018;Siffert & Schwarz, 2011), usually benefiting from sufficient emotional growth and positive psychological functioning (Siffert & Schwarz, 2011;Valladares Kahn et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…No que se refere aos delineamentos metodológicos, sete artigos foram de revisão de literatura ou teóricos (Antunes-Alves e De Stefano, 2013; Brown e James, 2014; Carr, 2014;Cicila et al, 2014;Ibaceta, 2011;McCollum et al, 2011;Stith et al, 2012). Dos estudos empíricos quantitativos, cinco tinham delineamento explicativo (DeBoer et al, 2012;Froerer et al, 2012;Kahn et al, 2015;Rowe et al, 2011;Watkins et al, 2015) e um delineamento exploratório (Vall et al, 2015), sendo que, nesses estudos, todos os participantes eram casais heterossexuais. Considerando os estudos empíricos qualitativos, dois estudos tinham delineamento exploratório (Karakurt et al, 2013;Vall et al, 2014) e um foi etnográfico (Martinez et al, 2011).…”
Section: Resultsunclassified
“…Evidenciando dados favoráveis à utilização de terapia com casais violentos, pesquisadores da área referem que a terapia de casal reduz a agressão entre parceiros e também aumenta a percepção de segurança na relação, ainda que essas mudanças não estejam necessariamente correlacionadas (Kahn et al, 2015). Aponta-se também que a terapia em conjunto pode ser direcionada tanto para que o perpetrador assuma a responsabilidade pela agressão quanto para auxiliar os parceiros a desenvolverem capacidades mútuas de resolução de conflitos (Antunes-Alves e De Stefano, 2013).…”
Section: Resultsunclassified
See 1 more Smart Citation